Poesia expandida : a escrita poética no ciberespaço - Matia, Kátia Caroline de (2013)
The purpose of this dissertation was to conduct a study about the called digital poetry, focusing on its characteristics as a type of fictional production that occurs in cyberspace and is related to cyberculture, the cultural context of new technologies (LÉVY, 1999). Digital poetry is a type of poetic production that requires, essentially, the computer and the internet for its production and for its reading, being, therefore, a cyberculture object. The bibliographic research about the subject was made based on authors such as Antonio (2008, 2010), Risério (1998) and Padin (1996). In their studies, we sought theoretical contributions about poetic texts. We emphasized the specificities of poetry and protocols of reading from Literary Theory (CULLER, 1999; D'ONOFRIO, 1995; JAUSS, 1983). Thus, we selected a corpus composed of seven digital poems produced by Brazilian authors and by one Portuguese author. Considering this corpus we identified recurring characteristics in digital poetry, such as: the word, the image, the sound, the motion and the interactivity. We sought to specify each of these elements based on the assumption that the material of poetry is historical: what changes in each time of the history is how this material is presented by poetry and how each technique developed in the course of the history is also material to the poetic production. Due to be produced in a writing space that is the computer screen, digital poetry configures itself by expanding its significant elements, including semiotic systems different from written language, and therefore giving rise to new literacies.